Work Competency as a Strategic Determinant in Enhancing Employee Performance - Fahmi Kamal (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid advancement of digital technology has significantly transformed human life, enabling quick and easy access to information through sophisticated devices. This study aims to examine the influence of work competency on employee performance at PT Infomedia Nusantara in Jakarta. A quantitative approach was employed, using a random sampling technique to select 40 samples from a population of 66 permanent employees. Data were collected through a closed questionnaire, validated and analyzed using simple linear regression with Statistical Product and Service Solutions software version 28. The findings reveal that work competency significantly enhances employee performance, as indicated by the regression equation Y = 7.413 + 0.820X and a correlation coefficient of 0.827, suggesting a strong positive relationship. Work competency accounts for 68.4% of the variance in employee performance, with the remaining 31.6% influenced by other factors. In conclusion, organizations should prioritize competency development to improve performance, though limitations such as a small sample size and reliance on self-reported data suggest the need for broader, longitudinal studies to enhance generalizability and reduce potential bias.